1,3-oxazepine compounds derived from azomethine: Synthesis, characterization and antibacterial evaluation - Mohammed, Issam Ahmed; Ahmed, Mahmood; Ikram, Rabia; Qadir, Muhammad Abdul; Hussain, Riaz (Colegio de Farmaceuticos de la Provincia de Buenos Aires, 2018)
Two azomethines, namely 2-methoxy-4-phenyliminomethyl-phenol (1) and 4-[(2,4-dinitro-phenyl)-hydrazonomethyl]-2-methoxy-phenol (2) were prepared between the reaction of vanillin with aniline and 2,4-dinitrophenylhydrazine, respectively. Subsequently, these two azomethines were reacted via direct cyclic addition with maleic anhydride, phthalic anhydride and succinic anhydride, respectively, yielded a series of new 1,3-oxazepines (3-8). All the synthesized compounds were characterized on the basis of FT-IR, NMR, MS and elemental analysis (CHN). Disk diffusion and 96-well plate assay methods were employed for zone of inhibition and minimum inhibitory concentration determination respectively to investigate the antibacterial activities. Our studies showed that compound 5 showed promising antibacterial activities with zone of inhibition 24.7 mm against S. aureus, AI value 77.2 % compare to standard ciprofloxacin and MIC was 31.25 μg/mL.